PERAN MA’HAD UMAR BIN KHATTAB (MUBK) YOGYAKARTA DALAM PEMBELAJARAN BAHASA ARAB DAN MATERI KEISLAMAN - Susanti, Rina (ISTIQRA: Jurnal Hasil Penelitian, 2022)
This research aims to explore the role of the Arabic language course Institute, Ma'had Umar bin Khattab (MUBK) Yogyakarta in learning Arabic and Islamic materials for the community. For this purpose, this research was designed in the form of field research. Data collection techniques were carried out through observation and documentation, interviews, and filling out questionnaires. Data analysis is qualitative inductive, namely based on facts found in the field, then constructed into a hypothesis. The results of this research show that MUBK has played a real role in the process of learning Arabic and Islamic materials from 2002 until now, despite the Covid-19 pandemic. The form of this role can be seen in a structured Arabic language learning curriculum, clear programs, teachers who are competent in their fields and time flexibility are selling points that are "purchased" by those interested